2016
DOI: 10.1016/j.jde.2015.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Supersolutions for a class of nonlinear parabolic systems

Abstract: In this paper, by using scalar nonlinear parabolic equations, we construct supersolutions for a class of nonlinear parabolic systems including $$ \left\{\begin{array}{ll} \partial_t u=\Delta u+v^p,\qquad & x\in\Omega,\,\,\,t>0,\\ \partial_t v=\Delta v+u^q, & x\in\Omega,\,\,\,t>0,\\ u=v=0, & x\in\partial\Omega,\,\,\,t>0,\\ (u(x,0), v(x,0))=(u_0(x),v_0(x)), & x\in\Omega, \end{array} \right. $$ where $p\ge 0$, $q\ge 0$, $\Omega$ is a (possibly unbounded) smooth domain in ${\bf R}^N$ and both $u_0$ and $v_0$ are n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…which together with (4.2) implies that sup 0<τ <t/2 D\B(0,nt We prove Theorems 1.3, 1.4 and 1.5 by modifying the arguments in [8,10,14]. Lemma 5.1 is a key lemma in our proofs.…”
Section: This Together With (316) Implies Thatmentioning
confidence: 86%
See 1 more Smart Citation
“…which together with (4.2) implies that sup 0<τ <t/2 D\B(0,nt We prove Theorems 1.3, 1.4 and 1.5 by modifying the arguments in [8,10,14]. Lemma 5.1 is a key lemma in our proofs.…”
Section: This Together With (316) Implies Thatmentioning
confidence: 86%
“…Furthermore, they showed that, if problem (1.3) possesses a local-in-time nonnegative solution, then its initial trace µ satisfies the following: Here q θ := 1 + θ/N . In [8], developing the arguments in [10] and [14], they also obtained sufficient conditions on the initial data for the existence of the solution of (1.3) and identified the strongest singularity of the initial data for which the Cauchy problem to (1.3) possesses a local-in-time nonnegative solution.…”
Section: Introductionmentioning
confidence: 99%
“…It follows from (3.32) that We modify the arguments in [11] and [17] to prove Theorems 1.3, 1.4 and 1.5. In the rest of this paper, for any two nonnegative functions f 1 and f 2 defined in a subset D of [0, ∞),…”
Section: )mentioning
confidence: 99%
“…On the other hand, Takahashi [21] recently proved that, in the case p ≥ p * , for any γ > 0, Cauchy problem (1.2) The local solvability of Cauchy problem (1.2) has been studied in many papers (see e.g., [1,2,5,7,10,11,13,17,18,19,21,22,23] and references therein). It is known that there exists a constant c 2 > 0 such that Cauchy problem (1.2) possesses a solution in R N × [0, ρ 2 ], where ρ > 0, if p > p * and sup x∈R N µ L r,∞ (B(x,ρ)) ≤ c 2 with r = N (p − 1) 2 (1.3) (see [11]). See also [10,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…We introduce a simple but new supersolution (3.5), using J. In [8,10,20] similar functions were also used as supersolutions. However, these supersolutions were directly related to integrability conditions.…”
mentioning
confidence: 99%